Economic Status of the Aged Population: An Overview of Indian Literature - Hariharan, R. (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2017)
This paper reviews the economics status of aged persons in India. Aged Persons will be one of the major policy concerns of the twenty-first century. Population ageing will affect every single individual of the society in many ways. The review analysed economic status of the aged persons based on their family status, income status before and after retirement, saving and borrowing status of the aged persons in India. As the country is ageing, this will affect the economy, because the economic needs of the society will be different in an ageing society. Every ageing nation suffers from over dependency and lesser participation of younger Human Resources in productive processes. It is felt that the retired ageing populations start using the nation’s resources for social security needs, which is estimated to be a big burden on the exchequer of the state. Thus, the impact of ageing on Indian economy is multi-faced, which includes production, consumption, labour force and social expenditure on retirement. The developed world has already witnessed this and is looking for options to overcome this problem. However, this trend clearly reveals that aged persons will be a very big issue to the future society and vast resources need to be directed towards the support and care of the aged population. Thus, the present paper suggests the researchers in the field of aged population and their economics status to bring various researches for improving their economics status and assure the social status ofaged population.